Mechanical properties and environmental stress cracking resistance of rubber toughened polyester/clay composite - Bonnia, Noor Najmi; Ahmad, S. H.; Surip, Siti Norasmah; Nurul, S. S.; Hassan, Noorazlina; Anuar, Hazleen (Trans Tech Publications, Switzerland, 2012)
Crosslinked polyester clay nanocomposites were prepared by dispersing originically modified montmorillonite in prepromoted polyester resin and subsequently crosslinked using methyl ethyl ketone peroxide catalyst at different clay concentration. Cure process and the mechanical properties of rubber toughened polyester clay composite have been studied. Rubber toughened thermoset polyester composite were prepared by adding 3 per hundred rubber (phr) of liquid natural rubber (LNR) was used in the mixing of producing this composite. Modification of polyester matrix was done due to the brittle problem of polyester composite. Addition of LNR will increase the toughness of composite and produce ductile polyester. Two types of composites were produced which is clay-lnr polyester composite and clay polyester composite. Addition of liquid natural rubber significantly increased the impact strength and flexural properties. Result shows that addition of 6% of clay-lnr composite give good properties on impact, strength and flexural. From the ESCR test, both composites showed good resistance to environmental.